Environmental & architectural phenomenology. Vol. 8, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 1997)
Vol. 8, No. 3, Fall 1997 (includes “items of interest,” "citations received,” book review of Scott Russell Sanders' Staying Put, and essays by Hajo Neis, Christopher Gutsche, Robert M. Walsh, Eileen Tumlin, and Matthew Day).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals